The Interrelationship between Constitutional Justice and the Protection of the Federal System - A Comparative Analytical Study - - Rahman, Shalaw Sabah Abdul; Aziz, Sardar Mulla (Journal of Legal and Political Studies, 2023)
The justice of constitutional judge in dealing with constitutional issues that occur between the federal and state governments, is a question of utmost importance for the countries with federal systems. The reason is that the success of federal system and achieving a constitutional balance between the two governments is based on the neutral role that is played by the constitutional judge to achieve constitutional justice. Therefore, the constitutional judge, in the interpretation process of the constitutional provisions related to the federal system and the relationship between the federal and state governments and their jurisdictions, shall basically choose an interpretation that is essentially consistent with the spirit of the federal constitution. The judge also shall ensure the fact that the federal government does not exceed the extent of the authority that is empowered to as well as the state government never transcends its jurisdictional limits. Thus, if the constitutional judge succeeds in achieving this aim, he/she will ensure that the constitutional justice is fully realized. The article argues that the view of the German Federal Constitutional Court is the most accurate and consistent with constitutional justice comparing with the judicial position which has been taken by the Iraqi Federal Supreme Court in settling federal constitutional disputes.
Keywords: justice of constitutional judge; constitutional issues; constitutional judge; federal system; constitutional disputes